Energy and environmental implications of using geothermal heat pumps in buildings: An example from north China. (20th November 2017) - Chang, Yuan; Gu, Yurong; Zhang, Lixiao; Wu, Chuyi; Liang, Liang
Abstract: Integration of renewable energy technologies and buildings is a step toward more energy efficient buildings in China. However, the life-cycle of energy and environmental emissions associated with geothermal resource use in buildings is not well understood. This study quantifies the life-cycle energy consumption and environmental pollutant emissions of geothermal heat pump (GHP) deployment in China using a university building as an example. A process-based hybrid life cycle inventory (LCI) modeling approach was used to enable a comprehensive system boundary for footprint accounting and to provide specific insights for the design and operation of the geothermal technology. The life-cycle energy of the GHP system was 192 TJ, and the life-cycle SO2, NOx, and greenhouse gas (GHG) emissions were estimated at 35 metric tons (MT), 45 MT, and 19130 MT CO2 e. The annual operational energy use of the GHP was 6.2 and 4.1 kWh per square meter floor area for building heating and cooling respectively. This was an energy use reduction of 84% and 83% compared to municipal heating and air conditioner cooling. The energy and GHG payback times of the GHP systems were 0.5 and 0.3 years respectively, and the facility is estimated to be economically cost-effective in 7.4 years. Highlights: We calculate the life-cycle energy and emissions of geothermal heat pump (GHP) utilization in north China. The hybrid life cycle inventory model is adopted for comprehensive and specific footprint calculations. GHP's life-cycle energy is 192 TJ, and is insensitive to transportation and construction energy. GHP's life-cycle SO2, NOx, and GHG emissions are 35 tons, 45 tons, and 19130 tons CO2e respectively. The energy, GHG and economic payback time of GHP systems is 0.5, 0.3 and 7.4 years respectively.